Are Carbon Emissions Associated with Stock Returns? - Aswani, Jitendra; Raghunandan, Aneesh; Rajgopal, Shiva (Review of Finance, 2024)
Abstract An influential emerging literature documents strong correlations between carbon emissions and stock returns. We re-examine those data and conclude that these associations are driven by two factors. First, stock returns are correlated only with unscaled emissions estimated by the data vendor, but not with unscaled emissions actually disclosed by firms. Vendor-estimated emissions systematically differ from firm-disclosed emissions and are highly correlated with financial fundamentals, suggesting that prior findings primarily capture the association between such fundamentals and returns. Second, unscaled emissions, the variable typically used in academic literature, is correlated with stock returns but emissions intensity (emissions scaled by firm size), an equally important measure used in practice, is not. While unscaled emissions represent an important metric for society, we argue that, for individual firms, emissions intensity is an appropriate measurement choice to assess carbon performance. The associations between emissions and returns disappear after accounting for either of the issues above.